Theory, Application, and Implementation of Monte Carlo Method in Science and Technology 2019
DOI: 10.5772/intechopen.89150
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Monte Carlo Simulation for Choosing High Efficient Detectors for Small-Field Dosimetry

Abstract: In this chapter, a detailed study on physics and methodology of small field dosimetry are reported. It introduces talking about how small radiation fields came into existence and the importance of accurate small-field dosimetry. In addition, it discusses small and long cavity theories for evaluating accurate dose response. It sheds the spot on pencil beam algorithms for evaluating dose response and uses Monte Carlo (MC) simulation in categorizing primary and scattering components of the radiotherapeutic photon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 117 publications
0
2
0
Order By: Relevance
“…The size of the source is generally less than 5 mm, and hence the loss of LCPE would occur for radiation beams with a radius less than 5 mm. 8 Other literature suggests there is dependence on focal spot size in small field dosimetry; however, such an effect can only be seen for extremely small fields (<5 × 5 mm 2 ). 5,9 Moigner et al, Liu et al and Czarnecki et al have shown that there is not much dependence on source sizes of different machines for small fields.…”
Section: Introductionmentioning
confidence: 97%
“…The size of the source is generally less than 5 mm, and hence the loss of LCPE would occur for radiation beams with a radius less than 5 mm. 8 Other literature suggests there is dependence on focal spot size in small field dosimetry; however, such an effect can only be seen for extremely small fields (<5 × 5 mm 2 ). 5,9 Moigner et al, Liu et al and Czarnecki et al have shown that there is not much dependence on source sizes of different machines for small fields.…”
Section: Introductionmentioning
confidence: 97%
“…However, small field beams have several unique physical properties that necessitate special care in measuring their absorbed doses to water 1 . The volume averaging effect, the lack of lateral charged particle equilibrium, and different detector responses due to beam quality differences are typical characteristics of small fields that necessitate meticulous handling 2–6 . The International Atomic Energy Agency and the American Association of Physicists in Medicine published TRS‐483, a code of practice for the reference and relative dosimetry of small fields, in 2017 2 .…”
Section: Introductionmentioning
confidence: 99%